Electronic properties of As2S3 thin films - Issabayev, B.Sh.; Almassov, N.Zh.; Aliakbarova, A.A.; Djolmasheva, U.K. (Recent Contributions to Physics, 2018)
In work as method of thermal evaporation in a vacuum thin amorphous films of As2S3 are received. Temperature dependences of conductivity of films are investigated. It is established that the temperature dependence of conductivity σ (T) of films, in the studied interval of temperatures 300 – 440 K has semiconductor character and is well described by exponential dependence of σ = Сexp(-Eσ/kT). From calculations of value of C, it is revealed, according to Mott’s theory that with reduction of thickness of films, the conductivity mechanism on the delocalized states is replaced with the hopping mechanism of conductivity on the localized states in "tails" of the resolved zones, and then on the conductivity mechanism by jumps of carriers of a charge on the localized states near Fermi’s level. Activation energy of conductivity Eσ of films makes about a half of optical band gap. Spectra of optical transmission of films are investigated. It is established that they have the spectral dependence of the transmission coefficient T, typical for noncrystaline semiconductors in the region of the optical transmission edge, consisting of the region of interband transitions, the exponential region and the region associated with absorption at various structural inhomogeneities. It is supposed that the exponential absorption edge is caused by electronic transitions between the localized states in tails of the bands, and density of states exponential decreases with energy.